Namibia : Report on the Observance of Standards and Codes (ROSC)-Data Module Substantive Update on Monetary Statistics. (IMF Staff Country Reports; Country Report ;, 2005)
This report on the Observance of Standards and Codes (ROSC) data module provides an assessment of Namibia's monetary statistics against the recommendations of the General Data Dissemination System complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. Based on the review of Namibia's statistical practices, the mission provided a set of recommendations designed to increase further Namibia's adherence to internationally accepted statistical practices. These recommendations, in the mission's view, would also enhance the analytical usefulness of Namibia's monetary statistics.